2015
DOI: 10.1242/jeb.125310
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition and molecular interactions change with depth in the avian stratum corneum to regulate cutaneous water loss

Abstract: The outermost 10-20 µm of the epidermis, the stratum corneum (SC), consists of flat, dead cells embedded in a matrix of intercellular lipids. These lipids regulate cutaneous water loss (CWL), which accounts for over half of total water loss in birds. However, the mechanisms by which lipids are able to regulate CWL and how these mechanisms change with depth in the SC are poorly understood. We used attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) to measure lipid-lipid and lipid-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Muñ oz-Garcia et al [5] suggested that, at low and moderate temperatures, polar cerebrosides form ordered structures with the ceramides and they might sequester water molecules in their sugar moieties, decreasing the diffusion of water vapour through the skin. However, at higher temperatures, molecular motion causes cerebrosides to release water molecules bound to their sugar moieties and thus water vapour diffusion through the SC increases [28]. We propose that the presence of cerebrosides in the SC of bats may play a role in maintaining skin flexibility and elasticity by allowing increased hydration, a property that is important for animals using flight Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…Muñ oz-Garcia et al [5] suggested that, at low and moderate temperatures, polar cerebrosides form ordered structures with the ceramides and they might sequester water molecules in their sugar moieties, decreasing the diffusion of water vapour through the skin. However, at higher temperatures, molecular motion causes cerebrosides to release water molecules bound to their sugar moieties and thus water vapour diffusion through the SC increases [28]. We propose that the presence of cerebrosides in the SC of bats may play a role in maintaining skin flexibility and elasticity by allowing increased hydration, a property that is important for animals using flight Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…Salamanders limit water loss through perfusion and vascular regression, which would also reduce the amount of blood delivered to the skin for gas exchange (Brown 1972;Burggren and Moallf 1984;Riddell et al 2019). In previous studies that examined gene expression in this experiment, salamanders without physiological flexibility constitutively express higher levels of ALOXE3 (Riddell et al 2019), a gene underlying the production of a lipid barrier to reduce water loss rates across the skin (Champagne et al 2015). Salamanders have the capacity to reduce desiccation risk by increasing the dermal barrier to water loss, but these responses likely constrain respiration over longer periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed a negative association with plasticity in r i and expression of the ALOXE3 , a gene associated with production of ceramides, a type of essential fatty acid in epidermal tissue 55 . Loss of function mutations in this family of genes results in pathological disorders associated with high transepidermal water loss 55 , and many mammals and birds rely on ceramides or related fatty acids to limit transepidermal water loss 52 . With lower production of ceramides, salamanders might then rely on vascular regression to regulate water loss.…”
Section: Discussionmentioning
confidence: 99%